Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - VII (Coleoptera: Hispinae). - Gaedike, Reinhard; Döbler, Helga (Contributions to Entomology = Beiträge zur Entomologie, 1971)
A catalogue of the subfamily of beetles Hispinae is presented, which gives a survey of the types of this subfamily in the collection of former Deutsches Entomologisches Institut.